Minimally Invasive Video-Assisted versus Minimally Invasive Nonendoscopic Thyroidectomy. (8th April 2014) - Fík, Zdeněk; Astl, Jaromír; Zábrodský, Michal; Lukeš, Petr; Merunka, Ilja; Betka, Jan; Chovanec, Martin
Abstract : Minimally invasive video-assisted thyroidectomy (MIVAT) and minimally invasive nonendoscopic thyroidectomy (MINET) represent well accepted and reproducible techniques developed with the main goal to improve cosmetic outcome, accelerate healing, and increase patient's comfort following thyroid surgery. Between 2007 and 2011, a prospective nonrandomized study of patients undergoing minimally invasive thyroid surgery was performed to compare advantages and disadvantages of the two different techniques. There were no significant differences in the length of incision to perform surgical procedures. Mean duration of hemithyroidectomy was comparable in both groups, but it was more time consuming to perform total thyroidectomy by MIVAT. There were more patients undergoing MIVAT procedures without active drainage in the postoperative course and we also could see a trend for less pain in the same group. This was paralleled by statistically significant decreased administration of both opiates and nonopiate analgesics. We encountered two cases of recurrent laryngeal nerve palsies in the MIVAT group only. MIVAT and MINET represent safe and feasible alternative to conventional thyroid surgery in selected cases and this prospective study has shown minimal differences between these two techniques.